1968
DOI: 10.1071/bi9680209
|View full text |Cite
|
Sign up to set email alerts
|

Gibberellin and the Growth of Peach and Apricot Fruits

Abstract: Levels of gibberellin in purified extracts from developing peach fruits were compared with rates of cell division and cell expansion in the fruit tissues. No gibberellin was found in the ovary before full bloom. Immediately after full bloom gibberellin activity was found in the seed, and later in the mesocarp and endocarp as well. Gibberellin concentration was closely correlated with the rate of cell expansion in each tissue, but not with cell division. Until the final growth phase, when activity was found onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

1978
1978
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 15 publications
3
23
0
1
Order By: Relevance
“…GA 3 application may have also induced auxin synthesis, responsible for acidifying the cell wall which enables the action of pH-dependent expansins (Choi et al 2006;Xie et al 2009). Jackson (1968) had previously observed that in some apricots and peach varieties a high gibberellin concentration is needed at the beginning of the growth curve to induce cell division and later in development in order to achieve cell expansion. In summary, supplying GA 3 at the beginning of pit hardening induced transcript accumulation of genes encoding proteins putatively involved in protein folding and protection of the endoplasmic reticulum (HSP40 er) and chloroplast (HSP17.8 ch), endomembrane transport (GTPase), as well as genes involved in cell wall loosening (Exp1, Exp2, Exp3, Exp4), contributing to the mechanism responsible for increased fruit size and prevention of woolliness after cold storage.…”
Section: Resultsmentioning
confidence: 98%
“…GA 3 application may have also induced auxin synthesis, responsible for acidifying the cell wall which enables the action of pH-dependent expansins (Choi et al 2006;Xie et al 2009). Jackson (1968) had previously observed that in some apricots and peach varieties a high gibberellin concentration is needed at the beginning of the growth curve to induce cell division and later in development in order to achieve cell expansion. In summary, supplying GA 3 at the beginning of pit hardening induced transcript accumulation of genes encoding proteins putatively involved in protein folding and protection of the endoplasmic reticulum (HSP40 er) and chloroplast (HSP17.8 ch), endomembrane transport (GTPase), as well as genes involved in cell wall loosening (Exp1, Exp2, Exp3, Exp4), contributing to the mechanism responsible for increased fruit size and prevention of woolliness after cold storage.…”
Section: Resultsmentioning
confidence: 98%
“…Conversely, mutant fruits with inadequate quantities of GA exhibited a series of distortions in floral development and general reproductive growth events [12, 9, 14]. Although the potential impact of GA in coordinating fruit development processes has already been acknowledged [1518], the mechanism by which these effects are achieved is still largely unknown. This may be due to the diversity of cross-talk between GA and other hormones, which are often species/organ/developmental stage-dependent [19].…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous systems which regulate these stages are not known, but several scientists have described regulating roles for hormones . Jackson [8] observed high gibberellin-like activity in the pericarp of fruits during Stage I . Ethylene production also occurs at relatively high rates at that time and 1-aminocyclopropane-1-carboxylic acid concentration peaks in the fruit [9,13,14] .…”
Section: Introductionmentioning
confidence: 99%